Slow Instillation of Cooled Lignocaine Gel: Does it Reduce Urethral Discomfort During Cystoscopy? - Basnet, Robin Bahadur; Shah, Arvind Kumar; Shah, Chitaranjan (Nepalese Medical Journal, 2019)
Introduction: Intraurethral instillation of 2% lignocaine hydrochloride is associated with discomfort and stinging sensation, especially to male patients. This study was aimed to determine whether slow instillation and cooled gel reduce this discomfort.Materials and Methods: A prospective randomized study was done comparing initial and procedural discomfort between 2% lignocaine instilled at room temperature and cooled to 4° C, and that instilled over 2 seconds and 10 seconds. Hundred and sixty male patients were divided into two groups of eighty each for the two studies.Results: Significant reduction in initial discomfort was observed with 10ml of 2% lignocaine hydrochloride cooled to 4° C and also when instilled over 10 seconds. Although procedural discomfort was also lesser in these two sets, it was not statistically significant.Conclusions: Discomfort, the most common complaint of male patients during rigid cystoscopy, can be reduced by slow instillation of lignocaine hydrochloride gel and also if the gel is cooled to 4° C.